The limits of judicial independence - Clark, Thomas S. 1980- (Cambridge; New York: Cambridge University Press, 2011)
"This book investigates the causes and consequences of congressional attacks on the U.S. Supreme Court, arguing that the extent of public support for judicial independence constitutes the practical limit of judicial independence. First, the book presents a historical overview of Court-curbing proposals in Congress. Then, building on interviews with Supreme Court justices, members of Congress, and judicial and legislative staffers, as well as existing research, the book theorizes that congressional attacks are driven by public discontent with the Court. From this theoretical model, predictions are derived about the decision to engage in Court-curbing and judicial responsiveness to Court-curbing activity in Congress. The Limits of Judicial Independence draws on illustrative archival evidence, systematic analysis of an original dataset of Court-curbing proposals introduced in Congress from 1877 onward, and judicial decisions. This evidence demonstrates that Court-curbing is driven primarily by public opposition to the Court, and that the Court responds to those proposals by engaging in self-restraint and moderating its decisions"--
Introduction -- A political history of court-curbing -- Conditional self-restraint -- Court-curbing and the electoral connection -- Public support and judicial review -- Ideological implications of court-curbing -- The limits of judicial independence.
Includes bibliographical references (p. 299-312) and index.
Keywords: United States. -- Supreme Court -- Public opinion; United States. -- Supreme Court -- History; Judicial independence -- United States; Judgments -- United States -- Public opinion